2011
DOI: 10.21608/jpp.2011.85576
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF IRRIGATION LEVELS AND RICE STRAW COMPOST RATES ON YIELD, CHEMICAL COMPOSITION AND WATER USE EFFICIENCY OF CABBAGE (Brassica oleraceae var. Capitata L.)

Abstract: Organic fertilizer and water management are essential factors for achieving adequate cabbage development and productivity. Two field experiments were conducted in a clay loam soil at a private farm located at Aga district, Dakahlia governorate, Egypt, during the two successive seasons of 2009 and 2010. The effect of three irrigation levels (35, 45 and 55% depletion from the available soil moisture), three rice straw compost rates (0, 5 and 10 ton/fed.) and their interactions were studied on yield, chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…The enhancement effect of compost on plant growth may be due to its effect on improving soil water holding capacity and soil structure and increasing availability of nutrients needed for plant growth as the experimental soil was sandy and poor in nutrients (Table 1) and the used compost contained considerable contents of organic matter and nutrients (Table 3). Such suggestions agreed with Rono et al (2003), Vimala et al (2006), Phallus and Marsono (2008), Ibrahim et al (2011) and Talkah (2008).…”
Section: Growth Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…The enhancement effect of compost on plant growth may be due to its effect on improving soil water holding capacity and soil structure and increasing availability of nutrients needed for plant growth as the experimental soil was sandy and poor in nutrients (Table 1) and the used compost contained considerable contents of organic matter and nutrients (Table 3). Such suggestions agreed with Rono et al (2003), Vimala et al (2006), Phallus and Marsono (2008), Ibrahim et al (2011) and Talkah (2008).…”
Section: Growth Parameterssupporting
confidence: 89%
“…Enrichment of compost with mineral NPK fertilizers could further increase the Chinese cabbage yield (Wei and Liu, 2005). Also, Ibrahim et al (2011) found that characters of cabbage cv. Balady Mohassan were significantly increased with increasing rate of rice straw compost.…”
mentioning
confidence: 98%
“…It has effects on photosynthesis, plant growth, production and quality. Several studies have shown that water deficit reduced crop growth, canopy development, morphological characteristics ( plant height, leaves fresh weight and head weight and dry matter accumulation) of cabbage plant ( Ibrahim et al, 2011;Nyatuame et al, 2013 andXU andLeskovar, 2014). In addition, maximum leaf area, curd weight, curd dry matter % values of broccoli plants were found in subjected to full irrigation treatment (Erken et al, 2013 andTangune et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…At the beginning of the experiment, all treatments were fully irrigated until 50 days from transplanting. In this period, irrigation was adjusted to reach the field capacity, and irrigation was optimized to reach the assumed field capacity (10-12 days) based on meteorological conditions (Ibrahim et al, 2011). Thereafter, all experimental plots were divided into three main groups, the first was irrigated at 10 days interval (7 irrigations) and the second was irrigated at 15 days interval (5 irrigations), while the third was irrigated at 20 days interval (3 irrigations) for I1, I2 and I3, respectively .…”
Section: Irrigation Treatments Optimizationmentioning
confidence: 99%
“…Irrigation should be managed concurrently to maximize yield, quality and irrigation efficiency for cabbage (McKeown et al, 2010). Increasing the water application, increased significantly cabbage head diameter, head weight, leaf weight and marketable yield (Sammis et al, 1988& 1989, A. Y. RAMADAN AND M. M. OMAR AbdelRahman et al, 1994, Parmar et al, 1999, AL-Rawahy et al, 2004, McKeown et al, 2010and Ibrahim et al, 2011. Agricultural scientists suggested the potential use of antitranspirants to enhance the yield of agronomic crops exposed to water stress during growth (Nickell, 1982 andFenton, et al, 1982).…”
Section: Introductionmentioning
confidence: 99%